Implementasi Nilai-Nilai Tasawuf dalam Menghadapi Era Globalisasi di Pondok Pesantren - Burhani, A. Roisul; S. Ahmad Alwi (Afkaruna: International Journal of Islamic Studies (AIJIS), 2023)
In this era of globalization, there are many crises that befall human life, ranging from social crises, structural crises, to spiritual crises. It all starts with the question of the meaning of human life. The rapid progress of technology and industrialization has resulted in humans losing their sense of direction. Material wealth continues to accumulate, but the soul experiences emptiness. Along with increasingly modern logic and orientation, work and materials have become an actualization of people's lives. This research aims to determine and analyze the factors and values ​​of Sufism in facing the era of globalization at the Tajul Alawiyin Islamic Boarding School. This research uses qualitative methods with several supports such as observation, interviews and documentation. The findings show that the implementation of Sufism values ​​in facing the era of globalization at the Tajul Alawiyin Islamic Boarding School is through several teachings to always have the qualities of patience, khauf, raja', zuhud, fakir and repentance. In the current era of increasingly advanced globalization, it does not create obstacles for students to practice the teachings of Salaf ulama. This has proven that the teachings of ulama remain relevant following the plurality of times and the modernity of today's society.